2022
DOI: 10.18203/2349-2902.isj20220372
|View full text |Cite
|
Sign up to set email alerts
|

Role of C-reactive protein in acute pancreatitis: an observational study in a tertiary care centre

Abstract: Background: Acute pancreatitis is significant reason for intense abdominal torment. The job of diagnostic markers (pancreatic enzymes like amylase and lipase) as prognostic pointers has been a disappointment. C-reactive protein (CRP) assessment is modest and effective option. In this concentrate we have endeavored to check whether a solitary and early assessment of CRP levels is a viable indicator of morbidity and mortality in acute pancreatitis.Methods: This was a prospective observational study done at Gover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
0
3
1
Order By: Relevance
“…9 In another study investigating the effect of CRP on prognosis in acute pancreatitis, it was found that CRP was higher in patients with local complications present on computed tomography, but it was not statistically significant. 14 In our study, there was a statistically significant relationship between high RDW and CRP and mortality, but although high neutrophil and low lymphocyte levels were evident in non-surviving patients, there was no statistically significant relationship between high neutrophil levels and low lymphocytes and mortality. There was a statistically significant correlation between low albumin and mortality.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…9 In another study investigating the effect of CRP on prognosis in acute pancreatitis, it was found that CRP was higher in patients with local complications present on computed tomography, but it was not statistically significant. 14 In our study, there was a statistically significant relationship between high RDW and CRP and mortality, but although high neutrophil and low lymphocyte levels were evident in non-surviving patients, there was no statistically significant relationship between high neutrophil levels and low lymphocytes and mortality. There was a statistically significant correlation between low albumin and mortality.…”
Section: Discussioncontrasting
confidence: 64%
“…10,11 Some studies have previously been conducted to evaluate the association of RDW with a poor prognosis in patients with pancreatitis, mostly comparing patients with pancreatitis with patients without pancreatitis. 2,6,9,[12][13][14] The relationship of RDW with mortality was also investigated in patients with acute coronary syndrome, acute appendicitis with inflammation similar to acute pancreatitis, infective diseases such as COVID-19, and malignancies. 11,[15][16][17] It can be quite difficult to predict the prognosis of acute pancreatitis, which has many causes, including idiopathic, especially in geriatric patients.…”
Section: Introductionmentioning
confidence: 99%
“…Further research is needed to better understand the role of CRP in mitigating the mortality and morbidity associated with AP. [89] Patients with severe pancreatitis exhibited a more significant elevation in CRP levels. One day after admission, the average CRP level was 280 mg/L in patients with hemorrhagic pancreatitis and 45 mg/L in those with mild pancreatitis.…”
Section: Clinical Studiesmentioning
confidence: 98%
“…Further research is needed to better understand the role of CRP in mitigating the mortality and morbidity associated with AP. [89]…”
Section: Inflammatory Markers In Pancreatitismentioning
confidence: 99%